From Floris to Rubens : master drawings from a Belgian private collection - Hautekete, Stefaan; Hautekete, Stefaan (Snoeck, 2016)
Published on the occasion of an exhibition featuring ninety drawings from artists from the southern and northern Netherlands created during the 16th and beginning of the 17th century. In addition to beautiful sketches for prints, paintings, stained glass and tapestries by great masters such as Frans Floris and Peter Paul Rubens, other sheets like the sublime figure studies of Hendrick Goltzius and Cornelis De Vos or the so accurately detailed landscapes of Pieter Stevens and Adriaen Frans Boudewijns are put in the spotlights. The majority of the selected drawings have never been shown to the public before. Exhibition: Koninklijke Musea voor Schone Kunsten van België, Brussels, Belgium (20.01-15.05.2016)